2006
DOI: 10.1111/j.1440-1843.2006.00849.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of peroxiredoxin and thioredoxin in human lung cancer and paired normal lung

Abstract: The upregulation of Prx I, Prx III and thioredoxin in lung cancer tissue may represent an attempt by tumour cells to adjust to the microenvironment in a manner that is advantageous to survival and proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
69
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 27 publications
(29 reference statements)
6
69
2
Order By: Relevance
“…In contrast, we found a reduced expression of peroxiredoxin 6 as a result of auranofin treatment. Peroxiredoxins are increased in a number of cancers, including lung cancer [53], and have been correlated to radioresistance and resistance to cisplatin [54] The peroxiredoxins also influence a variety of cellular processes that are sensitive to reactive oxygen species and play a role in signal transduction and gene expression related to alteration in cellular reactive oxygen species levels [55]. In many cases increased peroxiredoxin expression correlated to chemoresistance; our results suggest that treatment with both drugs, modifying the expression of peroxiredoxin, disrupts total cellular redox homeostasis and induces apoptosis.…”
Section: Functional Roles Of the Identified Proteinsmentioning
confidence: 99%
“…In contrast, we found a reduced expression of peroxiredoxin 6 as a result of auranofin treatment. Peroxiredoxins are increased in a number of cancers, including lung cancer [53], and have been correlated to radioresistance and resistance to cisplatin [54] The peroxiredoxins also influence a variety of cellular processes that are sensitive to reactive oxygen species and play a role in signal transduction and gene expression related to alteration in cellular reactive oxygen species levels [55]. In many cases increased peroxiredoxin expression correlated to chemoresistance; our results suggest that treatment with both drugs, modifying the expression of peroxiredoxin, disrupts total cellular redox homeostasis and induces apoptosis.…”
Section: Functional Roles Of the Identified Proteinsmentioning
confidence: 99%
“…Specifically, increased PRX expression has been reported in several studies of both lung cancer and breast cancer (Noh et al 2001;Park et al 2006). With respect to human lung cancer, differential PRX expression was reported for various tumor subtypes, including adenocarcinoma and high-grade squamous cell carcinoma, as well as advanced tumor stages (Chen et al 2006).…”
Section: Links Between Chemotherapy Resistance and Prx Activitymentioning
confidence: 99%
“…With respect to human lung cancer, differential PRX expression was reported for various tumor subtypes, including adenocarcinoma and high-grade squamous cell carcinoma, as well as advanced tumor stages (Chen et al 2006). Interestingly, modified (presumably oxidized) PrdxI accumulates in human lung cancer samples (Park et al 2006), indicating, perhaps, a role for the chaperone function of PrdxI in tumorigenesis (or elevated peroxide signaling). Furthermore, a recent study reported that increased Srx expression deregulates PrdxIV activity in lung cancers, and Srx and PrdxIV were found to be required for several key aspects of tumor growth and metastasis; e.g., anchorage-dependent colony formation, cell migration, and invasion (Wei et al 2011).…”
Section: Links Between Chemotherapy Resistance and Prx Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…From these reports and our former study, Prdx1 appears to have a possible correlation with an anti-tumor effect by producing epigenetic changes in cancer patients. On the other hand, some researchers have mentioned that this protein may be involved with cell proliferation and tumor growth in several kinds of solid cancers (11)(12)(13)(14)(15).In order to contribute to the controversial discussion about the influence of Prdx1 expression in malignant tumors, we examined the expression of this protein in 114 cases of ESCC by immunohistochemistry and evaluated the correlations with the clinical parameters of ESCC to determine whether or not the expression of PrdxI in ESCC plays an important role in tumor progression. ONCOLOGY REPORTS 18: 867-871, 2007 867 Tumor suppressor Prdx1 is a prognostic factor in esophageal squamous cell carcinoma patients ISAMU HOSHINO, HISAHIRO MATSUBARA, YASUNORI AKUTSU, TAKANORI NISHIMORI, YASUO YONEYAMA, KENTARO MURAKAMI, HARUHITO SAKATA, KAZUYUKI MATSUSHITA and TAKENORI OCHIAI…”
mentioning
confidence: 99%